Determinants of consumer price inflation versus producer price inflation in Asia - Juthathip Jongwanich; Petchtharin Wongcharoen; Donghyun Park (Asian Development Bank (ADB), 2016)
We empirically examine and compare the determinants of producer and consumer price inflation in 10 Asian economies during 2000-2015. In this connection, we also investigate the pass-through of global oil prices, global food prices, and exchange rates to domestic producer and consumer prices. Overall, we find that cost-push factors such as oil and food prices are more important in explaining producer price inflation than consumer price inflation in the 10 Asian economies. On the other hand, for consumer prices, demand-pull factors still explain much of the inflation. Finally, we find that the passthrough of global oil prices, global food prices, and exchange rates tend to be higher for producer prices than consumer prices in Asia.
Keywords: E31; F43; O53; 330; Asia; commodity price shocks; consumer price; exchange rate; inflation; monetary policy; pass-through; producer price